Clinical profile and management of pyogenic liver abscesses in a tertiary care hospital - Gupta, Shyam K.; Rasool, Ashufta; Hela, Aamir H.; Goel, Rohit; Hussain, Zahur (International Journal of Research in Medical Sciences, 2019)
Background: Pyogenic Liver abscesses are potentially life threatening if left untreated. They pose a major Diagnostic and therapeutic challenge to modern world. Interventional radiology is becoming standard of care for liver Abscesses. Methods: All patients of pyogenic liver abscess admitted to Government Medical College and hospital Jammu, J and K, India from October 2018 to November 2019 were prospectively studied. Demographics, presentation, lab reports and management strategies were evaluated. Results: Total of 60 patients of pyogenic liver abscesses were studied with 81.7% males. Alcohol was found to be most common risk factor with 55% of patients being alcoholic. Right lobe of liver was involved in 66.7% of patients. Segment VI and VII were involved in 50% of patients. The most common clinical symptom was right upper quadrant pain (98.3%), followed by fever (91.7%). The most common clinical sign was right upper quadrant tenderness (91.7%). Percutaneous drainage with catheter placement was the most common and successful modality of management associated with least hospital stay. Conclusions: Pyogenic liver abscess is a rare but serious problem. Early diagnosis and treatment are necessary to avoid mortality. Percutaneous drainage along with I.V antibiotics is the best form of management.